Clinical and radiographic effectiveness of two filling pastes for pulpectomy in primary molars with necrotic pulp - Castillo-Blaz, Sally Esperanza (2025)
Objetive: To compare the effectiveness of two filling pastes METAPEX ® and MCM chemotherapy paste in the treatment of primary molars with necrotic pulp. Methods: A controlled clinical trial with paired data was conducted in 29 six-year-old patients diagnosed with necrotic pulp in their mandibular first primary molars. The children were treated with two molars with necrotic pulp. Two study groups were established: Group A, molars filled with METAPEX, and Group B, molars filled with MCM antibiotic paste. The children received treatment with one technique per session and were subsequently restored with a glass ionomer restorative (Ketac Molar Eaxymix®). These were evaluated clinically and radiographically over time under certain parameters to determine their effectiveness. Results: When comparing the clinical and radiographic effectiveness between the METAPEX and MCM pulpectomy filling pastes, the values indicate that there is no significant difference between them p>0.05 Conclusion: Multibiotic paste (MCM) is highly effective in the treatment of patients diagnosed with pulp necrosis.